Navigating Through Crisis: How Digitalization Has Transformed Silver Craft SMEs in Batankrajan Village - Rahman, Hidayatur; Retnasih, Nora Ria (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
The COVID-19 pandemic, which began in 2020, has led to a decline in the performance of the SME sector. This study aims to determine the impact of digital transformation on silver handicraft SMEs in Batankrajan Village, Mojokerto Regency, in maintaining their businesses amid the unstable economic conditions caused by the COVID-19 outbreak. The research method used is descriptive qualitative, with primary data sources. This study employs interview techniques with informants selected through purposive sampling based on specific criteria. The results indicate that digital transformation has significantly influenced the business continuity of these SMEs. SME actors have leveraged digital platforms for marketing. With this strategy, the changes experienced by SMEs have been quite significant, as seen from the increased revenue and production compared to pre-pandemic levels. This study concludes that digital transformation plays a crucial role for silver handicraft SMEs in recovering post-pandemic income through digital platforms.